Validation of new genus the Miniagraecia (Orthoptera: Tettigoniidae) - Rentz, Dcf; Su, You Ning; Ueshima, N. (Zootaxa, 2012)
It has been pointed out that there is an error in our recent paper (Rentz et al., 2012). On p. 24 we designated Miniagraecia viridis Rentz, Su, Ueshima sp. nov. as the type species of the new genus Miniagraecia. However there is no such species. There was a manuscript change in the name of the species and we did not catch it in the type species designation. Miniagraecia is therefore a nomen nudum. Miniagraecia viridis is not a nominal species and Miniagraecia does not now have a fixed type species (International Code of Zoological Nomenclature, Article 67.1).